Personality‐based selection of entrepreneurial borrowers to reduce credit risk: Two studies on prediction models in low‐ and high‐stakes settings in developing countries. (28th September 2017) - Dlugosch, Thorsten Johannes; Klinger, Bailey; Frese, Michael; Klehe, Ute‐Christine
Summary: Small business growth is critical for economic development and poverty reduction in emerging markets, yet there remains an over $2 trillion gap in financing these entrepreneurs. This study explores the potential of personality assessments to help lenders solve this problem and lend to more entrepreneurs and contributes to psychological selection research by examining the effect of high versus low stakes on response distortions and predictive validity in a new area—entrepreneurship with a new dependent variable—paying back credit. Results of Study 1 show that personality assessments are indeed related to credit risk, but response patterns depend significantly on whether or not the assessment is taken as a mandatory part of the credit application (high stakes) or as an optional research survey after the credit has already been provided (low stakes), and predictive relationships do not generalize between these situations. In Study 2, the distributions of personality dimensions relevant for entrepreneurs applying for a credit—conscientiousness, extraversion, and integrity—are shown to be different for applicants when in high‐ versus low‐stakes settings. These findings convey several implications for the research on and practice of lending to entrepreneurs in emerging markets and offer new directions for future research.